TARGET CONTROLLING METHOD OF THE PRICING PROCESS IN THE TOURISM ENTERPRISES - N. Sagalakova (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
Key stages of the pricing process in the tourism enterprises are investigated: subprocess of establishing of nominal value of the new tourism product price and subprocess of adjustment of the established price depending on a situation in the tourism market. For establishing of nominal value of the price it is offered by use of optimizing model, which maximizes the usefulness function of structural parts of the tourism product price. For adjustment of the tourism product price under change of external conditions procedure of installation of the target with use of the process behavior charts of the pricing process is applied. The new methodology of the pricing process controlling in the tourism enterprises, which based on complex application of methods of the statistical processes control and a method of dynamic programming, is presented in article and fully considers one of key features of the tourism sphere - seasonal fluctuations of the tourism product price.